2013
DOI: 10.1097/rlu.0b013e31827a2325
|View full text |Cite
|
Sign up to set email alerts
|

68Ga DOTATATE PET/CT Uptake in Spinal Lesions and MRI Correlation on a Patient With Neuroendocrine Tumor

Abstract: A 62-year-old female patient with suspected insulinoma underwent 68Ga DOTA-TATE PET/CT for characterization and staging. This demonstrated a focus of uptake in the pancreas and 3 foci of uptake in the spine. An MRI of the spine performed to further characterize the lesions revealed the presence of a meningioma and degenerative changes, both of which showed 68Ga DOTA-TATE uptake. A vertebral metastasis seen on PET was occult on CT and MRI. A vertebral hemangioma had no discrete tracer uptake. Awareness of sourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 6 publications
0
16
0
Order By: Relevance
“…Other ligand-targeted radioimaging agents in human clinical trials include somatostatin analogues that are linked to radionuclide-chelating agents, such as edotreotide (DOTATOC), DOTATATE (tetraazacycl ododecane tetraacetic acid-octreotate; NCT01873248 and NCT01967537) and DOTANOC (DOTA-(tyrosine 3)-octreotide; NCT01747096) (FIGS 6,7; TABLE 2), which are being used to image neuroendocrine tumours [188][189][190][191] . SSTR2-targeted radiotherapeutics that use lutetium-177 and yttrium-90 are also currently under evaluation 192,193 .…”
Section: Ligand-targeted Imaging Agentsmentioning
confidence: 99%
“…Other ligand-targeted radioimaging agents in human clinical trials include somatostatin analogues that are linked to radionuclide-chelating agents, such as edotreotide (DOTATOC), DOTATATE (tetraazacycl ododecane tetraacetic acid-octreotate; NCT01873248 and NCT01967537) and DOTANOC (DOTA-(tyrosine 3)-octreotide; NCT01747096) (FIGS 6,7; TABLE 2), which are being used to image neuroendocrine tumours [188][189][190][191] . SSTR2-targeted radiotherapeutics that use lutetium-177 and yttrium-90 are also currently under evaluation 192,193 .…”
Section: Ligand-targeted Imaging Agentsmentioning
confidence: 99%
“…Somatostatin receptors are expressed by both normal pituitary gland and pituitary tumor. Novel 68 Ga-labeled somatostatin analogs, such as 68 Ga-DOTATATE, are now finding increasing clinical application (9)(10)(11)(12)(13)(14). Previously we reported that 68 Ga-DOTATATE in general had a higher uptake in the remaining pituitary tissue than in the recurrent or residual adenoma.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, only one case of 68 Ga-DOTATATE uptake in a spinal meningioma has been reported so far. [5] In that case, 68 Ga-DOATATE uptake was noted in a spinal meningioma of a patient suffering from insulinoma. In that case, unspecific uptake of 68 Ga-DOTATATE was observed in a degenerative lesion, which characterizes a potential pitfall in such investigations.…”
Section: Discussionmentioning
confidence: 91%